2009
DOI: 10.9775/kvfd.2009.543
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Left Sided Abomasal Displacement in Cattle by Laparoscopic Surgery

Abstract: Bu araştırmada, laparoskopik repozisyon ve Toggle pin fikzasyonu ile tedavi edilen sola abomasum deplasmanlı 28 inekte, intra ve postoperatif bulguların değerlendirilmesi hedeflendi. Laparoskopik cerrahi iki aşamada gerçekleştirildi. Birinci aşamada, hayvan ayakta iken abomasum içine Toggle pin yerleştirildi ve hemen ardından gaz ve sıvı içeriği dışarı alınarak deplase olan abomasumun repozisyonu sağlandı. İkinci aşamada, hidrolikli operasyon masasına sırt üstü yatırılan ineğin abdominal boşluğundaki Toggle pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…Constant et al (2018) and Nuss, (2011) found similar changes in the radiography of infected joints due to fluid and gas accumulation. Temizsoylu and Yigitarslan (2015) reported subchondral bone lysis, periostitis, osteomyelitis, and osteophytic formations in joint space in the case of chronic patients. Similar findings were observed for chronic cases in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Constant et al (2018) and Nuss, (2011) found similar changes in the radiography of infected joints due to fluid and gas accumulation. Temizsoylu and Yigitarslan (2015) reported subchondral bone lysis, periostitis, osteomyelitis, and osteophytic formations in joint space in the case of chronic patients. Similar findings were observed for chronic cases in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Small and large ruminants are most frequently affected by arthritis (Desrochers & Francoz, 2014). Depending on the severity of the disease, arthritis can affect a single joint, multiple joints, or even the entire body (Temizsoylu & Yigitarslan, 2015). Different degrees of distortion in the joint's parts occur in septic arthritis, leading to functional issues, including lameness, trouble standing, swelling, and discomfort (Haerdi-Landerer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Saha şartlarında güvenle kullanıla-bilen laparoskopik tekniklerin en öne çıkan dezavantajı ise laparoskopik ekipmanın pahalı olması ve manipülasyonu için belirli bir deneyim gerektirmesidir. 3,4 Sahada karşılaşılan abomasumun sola deplasmanı vakalarının tedavisinde laparotomi ve laparoskopi gibi cerrahi yöntemler yerine daha basit bir yöntem seçilebilir. Bu teknik veteriner hekimlerin sahada sıklıkla kullandıkları ve "toggle pin fiksasyonu" veya "kör dalış" olarak da bilinen "perkütan paramedian abomasopeksi" işlemidir.…”
unclassified